Optimizing Evacuation in Densely Populated Buildings: A Bottleneck Analysis - Topraklı, Abdurrahman Yağmur; Satır, Muhsin Selçuk (Gazi University Journal of Science, 2025)
Safe and efficient evacuation from densely populated buildings during emergencies is crucial for ensuring human safety. This study analyzes potential evacuation bottlenecks in densely populated buildings using the newly constructed Ordu Annex Courthouse in Turkey as a case study. Employing Pathfinder simulations, pedestrian flow dynamics were modeled, and critical areas of congestion hindering evacuation efficiency were identified. The simulation results revealed that while 95% of occupants could evacuate within 316 seconds, the remaining 5% experienced significant delays, particularly due to bottlenecks at stairwells leading to exits. This finding highlights the importance of evacuation optimization in the design of densely populated buildings. The study proposes actionable design recommendations, such as adjustments to corridor widths, modifications to exit configurations, and strategic placement of flow-control elements, as strategies with the potential to improve evacuation times and enhance overall safety.